Aspergillus Mycetoma Causing Epiphora and Ipsilateral Facial Pain. (May 2017) - Kauh, Courtney Y.; Gentry, Lindell R.; Hartig, Gregory K.; Lucarelli, Mark J.
Abstract : Tearing is a frequently encountered chief complaint in an ophthalmologist's office. Certain associated atypical symptoms may warrant further workup. The authors present a case of a patient presenting with painful tearing which elicited further evaluation with CT imaging. This revealed a maxillary sinus fungus ball as the cause for the patient's tearing. Abstract : An uncommon cause is found for a commonly encountered ophthalmic complaint.